2019
DOI: 10.1002/mrm.27788
|View full text |Cite
|
Sign up to set email alerts
|

Vessel‐specific quantification of neonatal cerebral venous oxygenation

Abstract: Purpose: Noninvasive measurement of cerebral venous oxygenation (Y v ) in neonates is important in the assessment of brain oxygen extraction and consumption, and may be useful in characterizing brain development and neonatal brain diseases.This study aims to develop a rapid method for vessel-specific measurement of Y v in neonates. Methods: We developed a pulse sequence, named accelerated T 2 -relaxation-underphase-contrast (aTRUPC), which consists of velocity-encoding phase-contrast module to isolate pure blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…16 For aTRUPC, although changes in T 1 will affect the signal evolution during the TFE acquisition train, it has been shown that this effect is negligible on Y v quantification. 17 There are several limitations of this study. First, although TRUPC and aTRUPC can measure Y v in multiple veins, we only compared the Y v in the SSS of TRUPC and aTRUPC with blood gas oximetry.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…16 For aTRUPC, although changes in T 1 will affect the signal evolution during the TFE acquisition train, it has been shown that this effect is negligible on Y v quantification. 17 There are several limitations of this study. First, although TRUPC and aTRUPC can measure Y v in multiple veins, we only compared the Y v in the SSS of TRUPC and aTRUPC with blood gas oximetry.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we validated the accuracy of both TRUPC and aTRUPC techniques. The TRUPC 16,17 method can be used when regional information is required and scan time is not a compelling issue. In applications in which Y v is expected to alter globally, aTRUPC can be a faster surrogate for TRUPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our Neurosciences Intensive Care Nursery specialists work together to establish protocols to promote neuroprotection and brain recovery from injury such as hypoxic-ischemic encephalopathy, stroke, intracranial hemorrhage, seizures, and central nervous system infections while also initiating measures that might prevent further injury, that is, optimizing brain perfusion, cerebral autoregulation, and oxygenation. [12][13][14][15][16][17][18][19][20] Standardization of video EEG monitoring during therapeutic hypothermia has resulted in improved rapid seizure detection, optimization of EEG recording techniques, and reduced use of unnecessary antiseizure medications in this vulnerable population. 21 Additional collaborative research has identified key imaging and clinical signs associated with long-term outcomes among preterm children with post-hemorrhagic hydrocephalus.…”
mentioning
confidence: 99%